Profiling the Extent and Location of Pain in Migraine and Cervicogenic Headache: A Cross-sectional Single-Site Observational Study. Issue 12 (11th September 2020) - Uthaikhup, Sureeporn; Barbero, Marco; Falla, Deborah; Sremakaew, Munlika; Tanrprawate, Surat; Nudsasarn, Angkana
Abstract: Objectives: The primary aim was to quantify and compare the location and extent of pain in people with either episodic migraine, chronic migraine, or cervicogenic headache. A secondary aim was to examine the associations between pain extent and headache features, quality of life, and psychological distress for each headache type. Design: A cross-sectional, single-site, observational study. Setting: Headache outpatient clinic. Subjects: From a sample of 390 patients, 114 patients with migraine or cervicogenic headache (48 episodic migraine, 30 chronic migraine, 36 cervicogenic headache) were eligible for the study. Methods: Pain location and extent were determined using a novel approach for digital pain drawing acquisition and analysis. Headache features included intensity and history duration. Quality of life was measured using the SF-36 and psychological distress using the Hospital Anxiety and Depression Scale. Results: Overall, pain was most frequently reported in the frontal and temporal regions in patients with either episodic or chronic migraine, whereas pain was most frequent in the suboccipital region in patients with cervicogenic headache. A larger pain extent was moderately correlated with higher headache intensity ( r s = 0.53, P  = 0.003) and poorer quality of life ( r s ranged from –0.36 to –0.40, P  < 0.05) in patients with chronic migraine, whereas pain extent was associated with longer headache duration in those with cervicogenic headache ( r s = 0.35, P  = 0.04). No correlation was found between pain extent and psychological features for any headache type ( P  > 0.05). Conclusions: Despite some differences, there was a large symptomatic overlap between headache types, highlighting the limitations of using pain location in the differential diagnosis of headache.